Prevalence of Vitamin K2 Deficiency and Its Association with Coronary Artery Disease: A Case–Control Study - Sameh A. Ahmed; Abdulaziz A. Yar; Anas M. Ghaith; Rayan N. Alahmadi; Faisal A. Almaleki; Hassan S. Alahmadi; Waleed H. Almaramhy; Ahmed M. Alsaedi; Man K. Alraddadi; Hussein M. Ismail (Diseases)
Background/Objectives: Vitamin K2 analogs are associated with decreased vascular calcification, which may provide protective benefits for individuals with coronary artery disease (CAD) by stimulating anti-calcific proteins like matrix Gla protein and adjusting innate immune responses. This study addresses a significant gap in understanding the association between serum levels of vitamin K2 analogs in different CAD types and examines their correlations with clinical risk parameters in CAD patients. Methods: This case–control study enrolled CAD patients and healthy controls to assess and compare serum concentrations of two vitamin K2 analogs including menaquinone-4 (MK-4) and menaquinone-7 (MK-7) via ultra-performance liquid chromatography with tandem mass spectrometry (UPLC-MS/MS). CAD risk factors were evaluated and related to serum levels of vitamin K2 analogs. The CAD group was further subdivided into stable angina, STEMI, NSTEMI, and unstable angina groups to investigate potential differences in vitamin K2 analog levels. Results: Patients experiencing acute coronary syndrome exhibited notably reduced serum levels of MK-4 and MK-7 (1.61 ± 0.66, and 1.64 ± 0.59 ng/mL, respectively) in comparison to the control group (2.29 ± 0.54, and 2.16 ± 0.46 ng/mL, respectively), with MK-4 and MK-7 displaying stronger associations with CAD risk indicators. Notable variations in vitamin K2 analog levels were found between CAD patients and control groups (p < 0.001). Unstable angina patients showed the lowest serum levels of MK-4 and MK-7. Conclusions: The present study demonstrated a higher prevalence rate of vitamin K2 deficiency among patients with CAD. The most pronounced decrease in MK-4 and MK-7 was observed in unstable angina patients. Moreover, these outcomes indicate the imperative requirement for an integrative approach that incorporates metabolic, lipid, and vitamin K2-related pathways in the risk stratification and management of CAD.